Computational Simulation of Tumor Surgical Resection Coupled with the Immune System Response to Neoplastic Cells. (30th December 2014) - Naveja, J. Jesús; Contreras-Torres, Flavio F.; Rodríguez-Galván, Andrés; Martínez-Lorán, Erick
Abstract : Numerous mathematical and computational models have arisen to study and predict the effects of diverse therapies against cancer (e.g., chemotherapy, immunotherapy, and even therapies under research with oncolytic viruses) but, unfortunately, few efforts have been directed towards development of tumor resection models, the first therapy against cancer. The model hereby presented was stated upon fundamental assumptions to produce a predictor of the clinical outcomes of patients undergoing a tumor resection. It uses ordinary differential equations validated for predicting the immune system response and the tumor growth in oncologic patients. This model could be further extended to a personalized prognosis predictor and tools for improving therapeutic strategies.